THE INFLUENCE OF WORK-LIFE BALANCE AND JOB SATISFACTION ON HEALTHCARE WORKER RETENTION IN HOSPITALS - Sonya Helen Maysha; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of work-life balance and job satisfaction on the retention of healthcare workers in Hospital X. The research adopts a quantitative approach with a descriptive and explanatory design. The population consists of healthcare workers, including doctors, nurses, and medical staff, while the sample is selected using a simple random sampling technique. Data were collected through a structured questionnaire measured using a Likert scale. The data analysis techniques include validity and reliability tests, classical assumption tests (normality, multicollinearity, and autocorrelation), multiple linear regression analysis, correlation analysis, coefficient of determination (R²), as well as hypothesis testing using t-test and F-test. The results show that work-life balance has a positive and significant effect on employee retention, and job satisfaction also has a positive and significant effect on employee retention. Simultaneously, both variables significantly influence employee retention. The coefficient of determination indicates that work-life balance and job satisfaction contribute significantly to explaining employee retention, while the remaining variation is influenced by other factors not examined in this study. In conclusion, improving work-life balance and job satisfaction is essential for enhancing the retention of healthcare workers. Hospitals are therefore encouraged to implement supportive policies and create a positive work environment to maintain a stable and committed workforce, ultimately improving the quality of healthcare services.